2022
DOI: 10.1088/1612-202x/ac6804
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mode-locked thulium/holmium-doped fiber laser assisted by bismuthene/side polished fiber as saturable absorber

Abstract: An all-fiber passively mode-locked laser is demonstrated near the 2.0 µm wavelength region utilizing thulium/holmium-doped fiber as the gain medium and bismuthene/side-polished fiber (SPF) as saturable absorber (SA). The effect of bismuthene concentration on the performance of the generated mode-locked lasers has also been investigated. In this work, bismuthene was obtained by the exfoliation of bismuth under the ultrasonication technique. Two different concentrations of bismuthene (10 and 20 mg ml−1) were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recently, bismuthene has received significant attention for its potential use in saturable absorbers thanks to its unique electron mobility properties, spin-orbit coupling, and incredible stability in ambient conditions [20,23,64]. In 2018, Guo et al first demonstrated a sub-200 fs soliton mode-locked fiber laser using bismuthene as the saturable absorber (Figure 3a) [16].…”
Section: Nonlinear Photonic Devicesmentioning
confidence: 99%
“…Recently, bismuthene has received significant attention for its potential use in saturable absorbers thanks to its unique electron mobility properties, spin-orbit coupling, and incredible stability in ambient conditions [20,23,64]. In 2018, Guo et al first demonstrated a sub-200 fs soliton mode-locked fiber laser using bismuthene as the saturable absorber (Figure 3a) [16].…”
Section: Nonlinear Photonic Devicesmentioning
confidence: 99%